Penerapan Metode Low Pass Filter (Lpf) Untuk Mengurangi Derau Pada Citra Magnetic Resonance Imaging (Mri) - Prakoso, Gilang Arif, Diah Priyawati,ST.M.Eng (2017)
MRI is a tool in the medical field who provide cross sectional imaging of the human body taken by the strong magnetic power and radio wave energy. MRI is used to detect abnormalities in human body parts. Often the results of MRI imaging there is noise that covers the area of detail of the image, it is necessary to noise reduction so that the image can be diagnosed properly or maximize the image analysis process. One method to reduce noise is the LPF. LPF is a filter that has passed the low-frequency properties and eliminates high frequency. Interest LPF method used for general noise has a high frequency value, then use LPF method aimed at eliminating high frequency caused by noise. Testing the use of LPF in this experiment using a Gaussian noise, Speckle noise, Salt and Pepper noise, and Rayleigh noise. So by using LPF method is expected to reduce noise and improve the quality of those produced by MRI imaging. After the image is free from noise, followed by the image of the validity of the measurement process by using Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE). PSNR is a method that compares the maximum value of the signal intensity measured by the amount of noise on the signal. While MSE is value-mean-square error between the original image with the image of the repair. So with PSNR and MSE will be able to assess the success of the LPF methods remove noise. LPF most effective method in reducing Salt and Pepper noise shown by the low value of MSE is 7.42 dB and a high value of PSNR is 39.46 dB. In addition built Graphical User Interface (GUI) application of MATLAB toolbox that can help facilitate research and document them for the sake of further research.